Artritida loketního kloubu - Guitton, Thierry G; Ring, David (Current Orthopaedic Practice, 2009)
Purpose of review: Improvements in medications, implant design, and arthroscopic techniques have changed the available treatment options for arthritic patients. The purpose of the present review is to explore recent developments and publications discussing the management of elbow arthritis. Recent findings: New medications have greatly reduced the role of surgery in the management of rheumatoid arthritis. Effective arthroscopic treatments are being developed for elbow arthritis, but it is difficult for more than a few surgeons to gain sufficient experience with these complex technical procedures. Several new concepts have influenced total elbow prostheses. Summary: The management of elbow arthritis is based on the type of arthritis and patient factors. The majority of operative treatments are palliative or reconstructive. As with arthritis in other joints, there is a stepladder of treatment options from nonspecific analgesia to arthroscopic or open debridement, interpositional arthroplasty, and ending with prosthetic arthroplasty, which is best reserved for relatively infirm and low-demand patients.
Keywords: výsledek terapie; Debridement; loketní kloub; Elbow Injuries; Therapeutics; osteoartróza; Athletic Injuries; nervus ulnaris; Arthralgia; poranění lokte; debridement; Wounds and Injuries; Plastic Surgery Procedures; medicína založená na důkazech; Drug Therapy; terapie; Ulnar Nerve; artroskopie; Arthroscopy; Osteoarthritis; artroplastiky kloubů; Treatment Outcome; výsledky a postupy - zhodnocení (zdravotní péče); Arthroplasty, Replacement; farmakoterapie; revmatoidní artritida; Arthritis, Rheumatoid; lidé; Humans; artralgie; Elbow Joint; Outcome and Process Assessment, Health Care; Evidence-Based Medicine; rány a poranění; zákroky plastické chirurgie; ortopedické výkony; sportovní úrazy; Orthopedic Procedures